2011
DOI: 10.1371/journal.pone.0016271
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal Proteomic Analysis of Retinal Protein Expression Alterations in a Rat Model of Diabetic Retinopathy

Abstract: BackgroundAs a leading cause of adult blindness, diabetic retinopathy is a prevalent and profound complication of diabetes. We have previously reported duration-dependent changes in retinal vascular permeability, apoptosis, and mRNA expression with diabetes in a rat model system. The aim of this study was to identify retinal proteomic alterations associated with functional dysregulation of the diabetic retina to better understand diabetic retinopathy pathogenesis and that could be used as surrogate endpoints i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 81 publications
6
50
0
Order By: Relevance
“…This group also described an increased expression of αB-crystallin in the cytoplasm of endothelial cells of epiretinal membranes in proliferative DR where it co-localized with VEGF (Dong et al, 2012). Several other reports in animal models of DR confirm an increase in αA- and/or αB-crystallin in the retina (VanGuilder et al, 2011; Kandpal et al, 2012). …”
Section: Changes In αB-crystallin Expression In Retina and Relatiomentioning
confidence: 80%
“…This group also described an increased expression of αB-crystallin in the cytoplasm of endothelial cells of epiretinal membranes in proliferative DR where it co-localized with VEGF (Dong et al, 2012). Several other reports in animal models of DR confirm an increase in αA- and/or αB-crystallin in the retina (VanGuilder et al, 2011; Kandpal et al, 2012). …”
Section: Changes In αB-crystallin Expression In Retina and Relatiomentioning
confidence: 80%
“…We again utilized a targeted biomarker approach, performing western blot analysis on a series of gene products that did not respond to insulin in a previous proteomic screen. 8 Protein levels of galectin-3 (Lgals3), STAT3, and annexin V have been shown to be upregulated in diabetic animals, yet insulin therapy does not significantly rescue this effect. 8 We found that both free and nanoliposomal minocycline were able to return STAT3 to prediabetic levels (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…8 Protein levels of galectin-3 (Lgals3), STAT3, and annexin V have been shown to be upregulated in diabetic animals, yet insulin therapy does not significantly rescue this effect. 8 We found that both free and nanoliposomal minocycline were able to return STAT3 to prediabetic levels (Figure 7). In addition, free minocycline caused galectin-3 to return to prediabetic levels, and liposomal minocycline caused annexin V to return to prediabetic levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two cohorts of male Sprague-Dawley rats were purchased at 100–125g body mass (Charles River, Wilmington, MA). After one week of quarantine, all rats were fasted overnight and diabetes was induced by intraperitoneal injection of 65mg/kg streptozotocin (STZ; Sigma Aldrich, St. Louis, MO) dissolved in 10mM sodium citrate (pH 4.5) as previously described (Bixler et al, 2011; VanGuilder et al, 2011). Non-diabetic (ND) control rats received the same treatment but were injected with an equal volume of citrate buffer.…”
Section: Methodsmentioning
confidence: 99%